Neuroprotective Effect of IRL-1620, an Endothelin B Receptor Agonist, on a Pediatric Rat Model of Middle Cerebral Artery Occlusion - Enrique G. Cifuentes; Mary G. Hornick; Suresh Havalad; Ramona L. Donovan; Anil Gulati (Frontiers Media S.A., 2018)
Objective: The purpose of this study was to determine the potential neuroprotective effect of endothelin B (ETB) receptor agonist IRL-1620 treatment in a pediatric model of ischemic stroke.Design: A prospective, animal model study.Setting: An experimental laboratory.Subjects: Three-month-old male Wistar Han rats.Interventions: The rats underwent permanent middle cerebral artery occlusion (MCAO). At 2, 4, and 6 h post MCAO, they were treated with saline, IRL-1620 (5 μg/kg, IV), and/or ETB antagonist BQ788 (1 mg/kg, IV).Measurements and Main Results: The rats were evaluated over the course of 7 days for neurological and motor deficit, cerebral blood flow (CBF), and infarct volume. Young rats treated with IRL-1620 following MCAO improved significantly in neurological and motor assessments as compared to the vehicle-treated group, as measured by neurological score (P = 0.00188), grip test (P < 0.0001), and foot-fault error (P = 0.0075). CBF in the infarcted hemisphere decreased by 45-50% in all groups immediately following MCAO. After 7 days, CBF in the infarcted hemisphere of the IRL-1620 group increased significantly (P = 0.0007) when compared to the vehicle-treated group (+2.3 ± 23.3 vs. −45.4 ± 10.2%). Additionally, infarct volume was significantly reduced in IRL-1620-treated rats as compared to vehicle-treated rats (P = 0.0035, 41.4 ± 35.4 vs. 115.4 ± 40.9 mm3). Treatment with BQ788 blocked the effects of IRL-1620.Conclusions: IRL-1620 significantly reduced neurological and motor deficit as well as infarct volume while increasing CBF in a pediatric rat model of cerebral ischemia. These results indicate that selective ETB receptor stimulation may provide a novel therapeutic strategy in the treatment of pediatric ischemic stroke as has been demonstrated in adult ischemic stroke.